2021
DOI: 10.31235/osf.io/zf6wy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racial Disparities in Mortality During the 1918 Influenza Pandemic in United States Cities

Abstract: The 1918 influenza pandemic stands out because of the unusual age pattern of high mortality. In the United States, another feature merits scientific scrutiny: against a historical backdrop of extreme racial health inequality, the pandemic produced strikingly small ratios of nonwhite to white influenza and pneumonia mortality. We provide the most complete account to date of these racial disparities in 1918, showing that, across U.S. cities, they were almost uniformly small. We examine four potential explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Concerns about infectious diseases are once again resurgent because of the COVID‐19 pandemic, with far‐ranging implications for changes to urban infrastructure (e.g., improved ventilation) and to the reorganization of public health resources within a city. Notably, research indicates that the health of cities during pandemics past and present is characterized by stark intraurban inequities, with the variation in mortality across racial groups during infectious disease outbreaks attributed in part to how health resources are allocated within cities 25–27 …”
Section: Key Themes In Urban Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about infectious diseases are once again resurgent because of the COVID‐19 pandemic, with far‐ranging implications for changes to urban infrastructure (e.g., improved ventilation) and to the reorganization of public health resources within a city. Notably, research indicates that the health of cities during pandemics past and present is characterized by stark intraurban inequities, with the variation in mortality across racial groups during infectious disease outbreaks attributed in part to how health resources are allocated within cities 25–27 …”
Section: Key Themes In Urban Healthmentioning
confidence: 99%
“…Notably, research indicates that the health of cities during pandemics past and present is characterized by stark intraurban inequities, with the variation in mortality across racial groups during infectious disease outbreaks attributed in part to how health resources are allocated within cities. [25][26][27] Looking beyond the pandemic, the epidemiological transition of the modern era will require a new paradigm for cities and population health, with a particular focus on improving chronic disease prevention and management. For example, policy interventions such as smoking bans or taxes on sugary beverages can align health promotion activities with the experience of city living.…”
Section: Key Themes In Urban Healthmentioning
confidence: 99%
“…Research on other racial and ethnic groups has focused on Black Americans. In a working paper, Eiermann et al ( 2021 ) report strikingly small differences in White versus non‐White mortality. However, other research has found that in the autumn of 1918, Black Americans had lower morbidity and mortality but higher case fatality than the White population (Crosby, 1976 , 2003 ; Økland & Mamelund, 2019 ).…”
Section: Evidence Of Morbidity and Mortality Disparitiesmentioning
confidence: 99%
“…Flu, another airborne disease, was the other most prevalent cause of infectious mortality during this period (Armstrong, Conn, and Pinner 1999). While recent research has begun to systematically explore racial inequality in flu mortality during the 1918 pandemic (Eiermann et al 2021), less is known about racial inequality in flu mortality generally.…”
Section: Datamentioning
confidence: 99%